Developing grammatical competence at the stage of pre-higher education training - Fisenko, Olga (2021)
The developing grammatical competence in teaching Russian as a foreign language foreign student at the stage of pre-higher education training is one of the most important tasks facing linguodidactics. The success of mastering Russian as a foreign language depends on the level of grammatical competence. Knowledge of grammar contributes to better mastering of Russian as a foreign language. The article defines the terminological status of competence, examines its correlation with such categories as linguistic competence, foreign language communicative competence, etc.There are described the principles of selection of educational material. There are highlighted the stages of work on communicative competence.